‘Karawakas, arba Krzizius anioliszkas’: A Versed Cross-Shaped Prayer in Lithuania - Drungilienė, Gita (Senoji Lietuvos literatūra, 2024)
The article deals with a versed cross-shaped prayer consisting of four lines (Crux mihi certa salus, crux est quam semper adoro. Crux Domini mecum, crux mihi refugium) and read letter by letter from the centre in all four directions. The origins of the text of the prayer go back to antiquity, and a little later the prayer was ‘encoded’ in the cross: it was written in the shape of the cross and became the best-known labyrinth of letters of the Middle Ages attributed to pattern or figured poetry (carmen figuratum). The prayer in the form of a cross was revived and spread in Europe during the Baroque period as the ‘Cross of St Thomas Aquinas’ that protects against thunderstorms, together with the ‘authorship’ attributed to this saint.The article analyses the signs of the functioning of this devotional tradition in Lithuanian society. The earliest translation of the prayer into Lithuanian, ‘Karawakas, arba Krzizius anioliszkas’ (Karawak, or the Angelic Cross), was published in 1817 as a one-sheet publication (print sheet). It is related to the Dominicans of Skapiškis and their missions (a special mention should be made of the contribution of Fr. Laurynas Bortkevičius, the then prior and promoter of the Way of the Cross); devotion itself could have spread through the Dominican environment. In the nineteenth century, devotion to St Thomas Aquinas’s cross kept reviving in Lithuania. The text of the prayer was published in Kiales Krizaus... (1819; Way of the Cross), a guide to the reflection on the Way of the Cross by the Dominicans of Skapiškis; in 1858 in Vilnius, the cross of St Thomas Aquinas was printed on a single sheet in Lithuanian and in Polish. There is information about another unsuccessful attempt to print a single sheet publication in 1860. The prayer ‘Crux mihi’ circulated in Lithuania in different languages and forms (onesheet prints, copies, and texts in prayer books; in the latter case, the link to the cross was retained in the title), and it was known under the titles of ‘Karawak’, the ‘Angelic cross’, and ‘St Thomas Aquinas’s Cross against the Thunderstorm’. However, so far, we can only speak of local centres of dissemination; translations of the prayer did not spread far and wide (the publisher of the 1858 edition was not aware of the earlier translation and did not use it; this edition contained more Polonisms, and it was the Polish text of the prayer that was written in the cross). The spread of ‘Karawakas’ in the Lithuanian public can be traced back to the devotion to the Way of the Cross in Skapiškis (having taken the form of a hymn, St Thomas Aquinas’s cross continued to function as a Lent hymn until the middle of the twentieth century), as well as to its apotropaic function (as is evident from the 1858 one-sheet print pasted on a wooden board). It is difficult to speak about the popularity of St Thomas Aquinas’s cross in Lithuania because the number of the surviving copies of the prints is extremely small (especially the one-page prints, in which this devotion unfolded to its fullest); this may also indicate its intensive use as an apotropaic sign in the face of imminent disasters and danger.
Keywords: St Thomas Aquinas’s cross; Crux mihi prayer; ‘Karawakas’; labyrinth of letters; Laurynas Bortkevičius; Dominicans of Skapiškis